2020
DOI: 10.14740/cr1137
|View full text |Cite
|
Sign up to set email alerts
|

Sacubitril/Valsartan Inhibits Cardiomyocyte Hypertrophy in Angiotensin II-Induced Hypertensive Mice Independent of a Blood Pressure-Lowering Effect

Abstract: Background: Hypertensive left ventricular hypertrophy is associated with the risk of heart failure, coronary heart disease and cerebrovascular disease. Although sacubitril/valsartan (SAC/VAL), a first-in-class angiotensin receptor neprilysin inhibitor, reduces the risks of death and hospitalization for patients with heart failure, its mechanism of action is not fully understood. We hypothesized that SAC/VAL is superior to other conventional drugs in reducing cardiac hypertrophy.Methods: Male C57BL/6J mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Similarly, TGF-β has been proposed to act in a paracrine/ autocrine manner between fibroblast and cardiomyocytes to stimulate cardiac remodeling (Leask, 2010). Valsartan, angiotensin receptor blocker, or Stachydrine mediated inhibition of Ang II/AT1 R/TGF-β signaling is a pivotal mechanism of anti-hypertrophic and anti-fibrotic effect (Teekakirikul et al, 2010;Liu et al, 2019;Tashiro et al, 2020). Ang II-induced fibrosis is associated with altered expression of inflammation-related genes such as TGF-β, TNF-α, MCP-1, IL-6, and type 3 collagen (Azushima et al, 2019).…”
Section: Angiotensin II In Cardiac Remodelingmentioning
confidence: 99%
“…Similarly, TGF-β has been proposed to act in a paracrine/ autocrine manner between fibroblast and cardiomyocytes to stimulate cardiac remodeling (Leask, 2010). Valsartan, angiotensin receptor blocker, or Stachydrine mediated inhibition of Ang II/AT1 R/TGF-β signaling is a pivotal mechanism of anti-hypertrophic and anti-fibrotic effect (Teekakirikul et al, 2010;Liu et al, 2019;Tashiro et al, 2020). Ang II-induced fibrosis is associated with altered expression of inflammation-related genes such as TGF-β, TNF-α, MCP-1, IL-6, and type 3 collagen (Azushima et al, 2019).…”
Section: Angiotensin II In Cardiac Remodelingmentioning
confidence: 99%
“…This anti-remodelling nature of ARNI is in agreement with data from other laboratories and large clinical studies. Sacubitril/valsartan prevented myocardial fibrosis and remodelling and improved cardiac function after myocardial infarction in mice [ 28 ] and rats [ 29 , 30 ], and in streptozotocin-induced diabetic hearts in mice [ 31 ]; it reduced cardiomyocyte size in Ang II-induced cardiac hypertrophy in mice [ 32 ], attenuated LV fibrosis and dysfunction in high-salt diet-induced diastolic dysfunction in rats [ 33 ], and reduced BP and prevented stroke in stroke-prone hypertensive rats [ 34 ]. A meta-analysis of clinical studies from 2010 to 2019 revealed that ARNI exerted reverse remodelling in terms of reduced LV size and hypertrophy compared with ACE inhibitors or AT1R blockers in patients with HF with a reduced LV ejection fraction [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It inhibited left ventricular hypertrophy in various models of cardiac hypertrophy, which was confirmed echocardiographically and histologically. Echocardiographic analysis revealed that sacubitril/valsartan decreased left ventricular wall thickness as shown by decreased interventricular septum thickness diameter, left ventricular posterior diastolic wall thickness, left ventricular mass, and left ventricular end-systolic diameter ( Chang et al, 2019 ; Zhao et al, 2019 ; Tashiro et al, 2020 ), leading to improved cardiac geometry ( Sung et al, 2020 ). Meanwhile, histological analysis showed that the increases in cardiomyocyte size induced by Ang II was significantly attenuated by the treatment ( Tashiro et al, 2020 ).…”
Section: Mechanistic Roles Of Sacubitril/valsartan In Cardiac Remodelingmentioning
confidence: 99%
“…Echocardiographic analysis revealed that sacubitril/valsartan decreased left ventricular wall thickness as shown by decreased interventricular septum thickness diameter, left ventricular posterior diastolic wall thickness, left ventricular mass, and left ventricular end-systolic diameter ( Chang et al, 2019 ; Zhao et al, 2019 ; Tashiro et al, 2020 ), leading to improved cardiac geometry ( Sung et al, 2020 ). Meanwhile, histological analysis showed that the increases in cardiomyocyte size induced by Ang II was significantly attenuated by the treatment ( Tashiro et al, 2020 ). However, a detailed molecular mechanism of sacubitril/valsartan inhibition on left ventricular hypertrophy was not fully characterized.…”
Section: Mechanistic Roles Of Sacubitril/valsartan In Cardiac Remodelingmentioning
confidence: 99%
See 1 more Smart Citation